Produção de biodiesel empregando catalisadores livres e suportados em matriz polimérica - Martins, Maria Inês (2015)
Due to social and environmental issues, considerable attention has been given to the production of biodiesel in substitution or addition of petroleum diesel. Biodiesel a mixture of fatty acids methyl esters is a renewable fuel obtained from a transesterification of vegetable oils and animal fats, in which alkaline hydroxides are used as catalyst. This process presents two main disadvantages: the catalyst cannot be reutilized or regenerated and there is a high quantity of residual water being produced during the separation fases. In this way, the production of biodiesel by means of heterogeneous catalytic transesterification becomes an interesting alternative in order to minimize the problems associated with homogeneous catalytic. In this respect, this study evaluates the production process of biodiesel by means of soybean oil methanolysis utilizing free and supported solid alkaline catalysts in a polymeric matrix. Initially, three distinct mixed oxides (Hidrotalcita de Mg/Al; CaO-CeO2 e CaZrO3) have been synthesized. These oxides were also supported in polysulphone (PS) and polyvinyl alcohol (PVA). The catalysts samples were physically and chemically characterized by different technics. These samples were then evaluated for their catalytic performance in the transesterification reaction, for pre-established conditions. It has been found that the CaZrO3 free and supported in PVA showed the best performance, attaining conversions greater than 90% in all conditions investigated. Thus, these two catalysts were selected for further experiments. It has been analyzed the influence of the operational conditions (methanol/oil molar ratio, temperature, amount of catalyst and time reaction) in the conversion of soybean oil into fatty acids methyl esters (% FAME). These conditions were optimized applying artificial neural network methodology in order to obtain the highest %FAME. Furthermore, it has been studied the behavior of different configurations of reactors (magnetic agitation, ultrasonic agitation with and without recirculation), the biodiesel synthesis in a spiral catalytic membrane and the stability of CaZrO3 free and supported in PVA. It is worth mentioning that under the studied conditions all variables presented significant influence in the %FAME. It is possible to conclude that under optimal conditions conversion above 96% FAME can be obtained for both catalysts under mild conditions of temperature and pressure (64°C and at atmospheric pressure). It was also found that the transesterification reaction under magnetic agitation resulted in higher mass transfer coefficients, either for the free catalyst or the supported one. This magnetic agitation prove to be more efficient then the ultrasonic agitation. The fact that the use of CaZrO3 in its free form has given the possibility of eight consecutive batch reaction cycles, which shows a high reuse capacity, without lixiviation, demonstrates its capability to be used successfully in continuous processes of biodiesel production. In conclusion, the use of a spiral catalytic membrane as a reactor presented satisfactory results (92,7 %FAME and 24 h reaction time) and thus confirming its viability to be used in the industrial production of biodiesel.